A new DC-DC Boost Converter Based on the Switch Capacitor Configuration with High Voltage Gain - Nghi Hoàng Tân; Dương Trương Khang; Trần Thành Nam; Hoàng Minh Đạt; Đỗ Đức Trí (Journal of Technical Education Science, 2025)
This paper presents a DC-DC boost converter configuration that is capable of providing a high DC output voltage based on the Switch Capacitor (SC) technique, referred to as a new DC-DC boost converter based on the switch capacitor configuration with high voltage gain (SCBC). The SCBC configuration is built on the traditional DC-DC boost converter, incorporating five capacitors and five diodes to enhance the voltage gain. The research configuration will generate a higher output voltage without requiring the power switch to operate with a large Duty Cycle (D). The notable feature of this configuration is its ability to triple the voltage gain compared to a traditional DC-DC boost converter. To validate the theoretical foundation presented in the paper regarding the circuit’s operating modes in Continuous Current Mode (CCM), simulations and experimental results were conducted with the assistance of PSIM software. The experimental model, featuring an input voltage of 29.3-V and an output voltage of 178-V, was tested in a laboratory setting. The small-signal model of the research configuration has been examined and analyzed in this paper, and the design of the PI control signal has also been constructed.